Incidence of chain of custody management in the ecuadorian criminal process - De La Torre Garcia, Pamela Michelle (2025)
The Chain of Custody is considered a fundamental element in criminal proceedings, since it depends on the validity that the judge comes. The Judicial Police, the Prosecutor's Office and all those responsible for the chain of custody must carry out their duties without any negligence, so that they are not involved in responsibilities that may be administrative, civil and even criminal. This study focuses on analyzing the elements to be taken into account in the management of the chain of custody in the Ecuadorian criminal process that guarantee the validity of the evidence. The importance of reviewing the topic lies in the need to know relevant aspects of the chain of custody and the evidentiary elements. It also includes information on the conditions and people involved in the stages of collection, shipment, handling, analysis and conservation of these elements, as well as possible changes that may have been made in each of these phases and by each person responsible for custody. A qualitative methodological approach has been adopted, oriented to normative, doctrinal and jurisprudential analysis and it is concluded that the chain of custody is an essential mechanism for the administration of justice in Ecuador, since it guarantees the authenticity, integrity and validity of the evidence in the criminal process.